Penyelesaian Sengketa Kedudukan Ahli Waris Pa’rinding Dalam Mewaris Berdasarkan Hukum Waris Adat Toraja - Sari, Ita Purwita; Santoso, Budi (Notarius, 2023)
AbstractInheritance law is one part of civil law as a whole and is the smallest part of family law. Inheritance problems in Indonesia often occur in every region, such as in Toraja, there is a form of inheritance distribution pa'rinding which is the giving of inheritance based on animal sacrifices at the time of the death ceremony of the testator. The problem is how the position of heirs pa’rinding inherits based on Toraja customary inheritance law and whether the decision of the Makale District Court panel of judges Number: 3-PDT.G-2015-PN.MAK regarding the position of heirs pa'rinding is appropriate or not according to customary inheritance law Toraja. This research method uses normative juridical, using secondary data through library research and primary data as complementary data conducted by interviews and qualitative data analysis with deductive conclusions. The position of heirs pa'rinding in Toraja is legally recognized and the heirs who are entitled to pa'rinding are those who are biological children of the heirs including adopted children. Court Decision Number 3-PDT.G-2015-PN.MAK is not in accordance with the provisions of customary inheritance law in Toraja regarding inheritance pa'rinding.Keywords: adat inheritance law; toraja adatAbstrakPermasalahan waris di Indonesia sering terjadi di setiap daerahnya, seperti di Toraja dikenal bentuk pembagian warisan secara pa’rinding yang merupakan pemberian harta warisan didasarkan oleh pengorbanan hewan pada saat upacara kematian pewaris. Artikel ini membahas mengenai bagaimana kedudukan ahli waris pa’rinding mewaris berdasarkan hukum waris adat Toraja serta apakah putusan majelis hakim Pengadilan Negeri Makale Nomor: 3-PDT.G-2015-PN.MAK tentang kedudukan ahli waris pa’rinding sudah sesuai atau tidak menurut hukum waris adat Toraja. Metode penelitian ini menggunakan yuridis normatif, menggunakan data sekunder melalui studi kepustakaan dan dara primer sebagai data pelengkap yang dilakukan dengan wawancara dan analisis data secara kualitatif dengan penarikan kesimpulan secara deduktif. Kedudukan ahli waris pa’rinding di Toraja diakui secara sah keberadaannya serta ahli waris yang berhak melakukan pa’rinding adalah mereka yang merupakan anak kandung dari pewaris termasuk anak angkat. Putusan Pengadilan Nomer 3-PDT.G-2015-PN.MAK tidak sesuai dengan ketentuan hukum waris adat di Toraja mengenai pewarisan secara pa’rinding.Kata kunci: hukum waris adat; adat toraja